Constraining X-ray emission in HBL blazars using multiwavelength observations - Wierzcholska, Alicja; Wagner, Stefan (Monthly notices of the Royal Astronomical Society, 2020)
ABSTRACT. The X-ray spectrum of extreme high-energy peaked BL Lac-type blazars is located in the synchrotron branch of the broad-band spectral energy distribut
Gesehen am 14.09.2020